Non-Traditional Rig for Virtual Environment Systems. Case study: Arm rig - Sierra Picon, Gabriel; Rocha Castano, Carlos Alberto; Sarmiento, Wilson J. (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2021)
This paper presents a case study of non-traditional skeleton rigs to solve candy wrapper problems in Virtual Environment systems. The approach tested is an alternative to traditional skeleton rigs used in animation processes, which may generate undesirable deformations in the mesh since they are usually made with handcrafted artistic animation in mind. In Virtual Environment systems, manual improving limbs' mesh deformation is not possible. This work includes promissory results in the naturalness of the deformation of the wrist of a digital character, validated with eight experts' subjective evaluations in 3D production.